Petition to confirm a consumer’s right to use Internet communications software and attach devices to wireless networks - Libertelli, Christopher; Goldberg, Henry; Kumar, Devendra T. (Law, State and Telecommunications Review, 2011)
As the wireless industry matures, consolidation and the relationship between handset manufacturers and carriers are producing market practices that raise substantial questions about whether consumers are receiving the maximum benefits of wireless competition. For example, carriers are beginning aggressively to influence software and product design to the detriment of consumers. As the wireless market has matured and wireless handsets become an integral part of most American’s lives, carriers are using their considerable influence over handset design and usage to maintain control over and limit subscribers’ right to run software communications applications of their choosing. Instead of carrying the subscribers’ messages indifferent to content, carriers have exerted more and more control over the way consumers access the mobile Internet. In an effort to prefer their own affiliated services and exclude rivals, carriers have disabled or crippled consumer-friendly features of mobile devices. Carriers are doing so, moreover, in violation of the Commission’s Carterfone principle and the strictures of the Commission’s original order permitting the bundling of consumer equipment and wireless service. The Commission should act now to enforce Carterfone and unlock the full benefits of wireless price competition and innovation. In light of these developments, Skype respectfully requests that the Commission make unmistakably clear that Carterfone will be enforced in the wireless industry, to initiate a proceeding to evaluate wireless carrier practices in light of Carterfone, and to create an industry-led mechanism to ensure the openness of wireless networks. Doing so will ensure both that consumers retain a right to run the applications of their choosing and attach all non-harmful devices to the wireless network. Finally, Commission involvement will ensure that carriers cannot use illegitimate network management practices as an excuse for otherwise anti-consumer behavior.